2011
DOI: 10.1007/s00018-011-0898-9
|View full text |Cite
|
Sign up to set email alerts
|

MAPK pathway activation in pilocytic astrocytoma

Abstract: Pilocytic astrocytoma (PA) is the most common tumor of the pediatric central nervous system (CNS). A body of research over recent years has demonstrated a key role for mitogen-activated protein kinase (MAPK) pathway signaling in the development and behavior of PAs. Several mechanisms lead to activation of this pathway in PA, mostly in a mutually exclusive manner, with constitutive BRAF kinase activation subsequent to gene fusion being the most frequent. The high specificity of this fusion to PA when compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(165 citation statements)
references
References 112 publications
6
157
2
Order By: Relevance
“…41,42 These fusions are only very rarely found in other tumours. KIAA1549:BRAF gene fusions are therefore considered a very important diagnostic aid to distinguish pilocytic astrocytoma from higher grade astrocytic tumours, a distinction that can be both challenging and therapeutically highly relevant given the fact that pilocytic astrocytomas and glioblastomas share the morphological feature of microvascular proliferation.…”
Section: Braf Fusion or Point Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 These fusions are only very rarely found in other tumours. KIAA1549:BRAF gene fusions are therefore considered a very important diagnostic aid to distinguish pilocytic astrocytoma from higher grade astrocytic tumours, a distinction that can be both challenging and therapeutically highly relevant given the fact that pilocytic astrocytomas and glioblastomas share the morphological feature of microvascular proliferation.…”
Section: Braf Fusion or Point Mutationmentioning
confidence: 99%
“…45 The glioma-associated BRAF alterations all exert their oncogenic activity by activating the mitogen-activated protein kinase (MAPK) pathway. 42 More recent studies employing large scale sequencing identified an oncogenic hit in the MAPK pathway in (almost) all pilocytic astrocytomas (Pfister, unpublished) while they did not reveal any significantly mutated gene outside of this pathway, indicating that this tumour may indeed be a single-pathway disease. The availability of small-molecule BRAF kinase inhibitors such as vemurafenib (PLX4032), which specifically targets BRAF V600E -mutant tumours, provides a new therapeutic approach to these subgroups of gliomas and preliminary clinical evidence (Pfister, unpublished) suggests that the presence of a BRAF V600E mutation may indeed serve as a potent predictive marker for this subset of patients across gliomas of various grades.…”
mentioning
confidence: 97%
“…However, their prognostic significance is unclear. KIAA1549-BRAF fusion causes a deletion of the amino-terminal domain of BRAF and constitutive activation of its kinase activity [44]. A proteomic study confirmed the predominance of the MAPK pathway for childhood PA and introduced novel findings regarding ERK-2 expression [6].…”
Section: Molecular Findingsmentioning
confidence: 94%
“…Nf1-PAs are usually less aggressive and located at extracerebellar sites [8] . The overall prognosis for PAs is good, but in some cases they are aggressive, leading to death [9][10][11] . Extension of resection and high mitotic activity are key factors related to a poor prognosis in PAs [10,11] .…”
Section: Introductionmentioning
confidence: 99%